An Autobiography of Novice Teacher in Using Multimodality for Teaching Reading to Young Learners - Maria Leswinda Wulan; N. A. Drajati; Sumardi Sumardi (Universitas Jambi, Magister Program of English Education Department, 2019)
This study is the author’s autobiography as a novice teacher in teaching fifth-grade students with multimodality. İ have been teaching young learners for five years in one of an elementary school in Indonesia. Until this day, I am still in the quest to find the best method to develop young learners’ reading proficiency. I also want to change their perspective about reading. İt is necessary to create a reading process which is enjoyable and not boring in the classroom. Young learners who were born in the 21st century, digital natives and non-traditional learners. Multimodality consists of several different modes. Each mode is meaningful and has a role. As a teacher, I could design each mode based on her students’ needs and what they were familiar with.